2015
DOI: 10.1128/aac.01437-15
|View full text |Cite
|
Sign up to set email alerts
|

VT-1161 Protects Immunosuppressed Mice from Rhizopus arrhizus var. arrhizus Infection

Abstract: We studied the efficacy of the investigational drug VT-1161 against mucormycosis. VT-1161 had more potent in vitro activity against Rhizopus arrhizus var. arrhizus than against R. arrhizus var. delemar. VT-1161 treatment demonstrated dose-dependent plasma drug levels with prolonged survival time and lowered tissue fungal burden in immunosuppressed mice infected with R. arrhizus var. arrhizus and was as effective as high-dose liposomal amphotericin B treatment. These results support further development of VT-11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 21 publications
2
40
0
1
Order By: Relevance
“…1. Consistent with historical data (14,15), 90% of placebo-treated mice died within 2 weeks of infection. Prophylaxis with VT-1161 but not POS protected mice from R. arrhizus var.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…1. Consistent with historical data (14,15), 90% of placebo-treated mice died within 2 weeks of infection. Prophylaxis with VT-1161 but not POS protected mice from R. arrhizus var.…”
supporting
confidence: 82%
“…In vitro testing has demonstrated that VT-1161 has intrinsic antifungal activity in the range of 0.12 to 1 g/ml against some molds, particularly against the order Mucorales (e.g., Rhizopus arrhizus var. arrhizus [14] (14). Our objectives in the present study were to measure the in vivo activity of VT-1161 prophylaxis or continuous therapy of murine mucormycosis caused by R. arrhizus var.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Following proprietary manipulation of this part of the molecule, compounds have now been developed that have substantially reduced interactions with cytochrome P450 and thus fewer potential drug– drug interactions. This platform has yielded several new compounds: VT-1161 (REFS 104,105), which is in phase II clinical trials for onychomycosis 106 and vaginal candidiasis (NCT02267356 and NCT02267382), and a very potent anti-cryptococcal compound, VT-1129, which has outstanding efficacy in vitro and in animal models 107 . Finally, in their portfolio is VT-1598, which is a potent azole, with activity against endemic mycosis (see the Business Wire press release ) and cryptococcosis.…”
Section: Improving Existing Antifungalsmentioning
confidence: 99%